Assessment Practices: Challenges and Opportunities Faced by EFL Teachers - Dian Fitriani (LINGUA: Jurnal Bahasa dan Sastra, 2019)
Abstract: Assessment is vital to education and plays important role in teaching and learning process. The Indonesian 2013 curriculum mandates the teachers to have a competence in assessing students’ learning either formative (assessment-for-learning) or summative assessment (assessment-of-learning) to enable students to develop themselves and have learning improvement as well. However, teachers of English, especially in Indonesia are facing challenges in carrying out assessment. This paper aims to review the challenges as well as the opportunities faced by teachers of English in classroom assessment practices. The challenges and problems coming from pedagogical competence include teachers’ knowledge of implementing assessment practices, the curriculum mandate, and tools in supporting teaching and assessment activity. Meanwhile, a good understanding of classroom assessment to decide the follow up actions is a trigger to make learning activities successful and meaningful for students.Keywords: Classroom assessment, challenges, opportunitiesAbstrak: Penilaian sangat penting untuk pendidikan dan berperan penting dalam proses belajar mengajar. Kurikulum 2013 di Indonesia mengamanatkan guru untuk memiliki kompetensi dalam menilai pembelajaran siswa baik formatif (penilaian-untuk-pembelajaran) atau penilaian sumatif (penilaian-pembelajaran) untuk memungkinkan siswa mengembangkan diri dan memiliki peningkatan pembelajaran. Namun, banyak guru Bahasa Inggris di dunia, termasuk di Indonesia menghadapi tantangan dalam melaksanakan praktik penilaian. Makalah ini bertujuan untuk meninjau tantangan serta peluang yang dihadapi oleh guru bahasa Inggris dalam praktik penilaian kelas. Tantangan dan masalah tersebut disebabkan kompetensi pedagogis termasuk pengetahuan guru tentang penerapan praktik penilaian, mandat kurikulum, dan alat dalam mendukung kegiatan pengajaran dan penilaian yang juga menjadi peluang dan tantangan bagi guru. Sementara itu, pemahaman yang baik tentang penilaian kelas untuk memutuskan tindakan tindak lanjut dapat menjadi pendorong untuk membuat kegiatan pembelajaran berhasil dan bermakna bagi siswa.Kata-kata kunci: Penilaian kelas, tantangan, peluang